2020
DOI: 10.24198/jkg.v32i2.26570
|View full text |Cite
|
Sign up to set email alerts
|

<p>Perbedaan ketinggian tulang kortikal mandibula antara penderita bruxism dan bukan penderita bruxism berdasarkan indeks panoramik mandibular</p><p>Differences in the mandibular cortical bone height between bruxism and non-bruxism patients based on the panoramic mandibular index</p>

Abstract: Pendahuluan: Bruxism adalah aktivitas parafungsi oklusal pada siang atau malam hari dimana terjadi grinding, clenching, dan gnashing. Bruxism dapat memberikan tekanan berlebih pada tulang sehingga tulang beradaptasi melalui proses remodeling tulang yang dapat mengubah jumlah, densitas, dan ketinggian tulang. Perubahan yang terjadi pada tulang dapat dianalisis dengan mengukur ketinggian tulang kortikal mandibula. Salah satu metode pengukuran yang dapat digunakan adalah indeks panoramik mandibula (PMI) melalui r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…As far as we know, there are few studies in the literature evaluating the bone quality of patients with bruxism using radiomorphometric indices on OPG [2,13,14,17]. The rst study reporting the relationship between radiomorphometric indexes and bruxism is Isman's study in 2020 [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as we know, there are few studies in the literature evaluating the bone quality of patients with bruxism using radiomorphometric indices on OPG [2,13,14,17]. The rst study reporting the relationship between radiomorphometric indexes and bruxism is Isman's study in 2020 [2].…”
Section: Discussionmentioning
confidence: 99%
“…Aziza et al [14], who measured the mandibular cortical bone height according to GI and AI on OPGs in 30 bruxer and 30 non-bruxer individuals, found that these two index values were not statistically different between bruxer and non-bruxer individuals. In another similar study, Fauziah et al [17] formed two groups: 30 digital OPG samples of patients with bruxism and 30 digital OPG samples of patients without bruxism. They reported that there was no signi cant difference in the height of the mandibular cortical bone between bruxism patients and non-bruxism patients based on PMI.…”
Section: Discussionmentioning
confidence: 99%
“…These changes should be considered when planning dental treatment in patients with bruxism Therefore, in our study, the effects of bruxism on bone mineral density and shape were evaluated using HU value and radiomorphometric indices (9). As far as we know, there are few studies in the literature evaluating radiomorphometric indices on DPRs of bruxism (7,(11)(12)(13). The first study reporting the relationship between radiomorphometric measurements and bruxism status is Isman's (2020) study (7).…”
Section: Discussionmentioning
confidence: 99%
“…The examination of panoramic radiography is conducted using several qualitative and quantitative indices, namely mandibular cortical index (MCI), mental index (MI), panoramic mandibular index (PMI), and gonion antegonial index. 10,12 PMI is an index that provides results in the form of a comparison between the thickness of the mandibular cortex and the distance from the inferior mental foramen to the inferior border of the mandibular cortex. Therefore, this measurement method allows calculations to be performed despite variations in magnification by different researchers.…”
mentioning
confidence: 99%
“…Therefore, this measurement method allows calculations to be performed despite variations in magnification by different researchers. 12,13,14 Based on the statement above, the researchers are interested in determining the differences in panoramic mandibular index values between male and female hypertensive patients using panoramic radiography.…”
mentioning
confidence: 99%